UVC-based advanced oxidation processes for water treatment: laboratory and pilot plant scale studies - Sánchez Montes, Isaac José (Universidade Federal de São Carlos, 2020)
The challenge of providing good-quality water free from contaminants of emerging concern (including organic microcontaminants; OMCs) and pathogens is one of the main hot topics worldwide. Thus, the efficiency of different UVC-based advanced oxidation processes (UVC AOPs) to remove organic pollutants and/or inactivate pathogens under distinct experimental conditions was investigated. At laboratory scale, UVC/HClO process showed the best performance for the degradation and mineralization of BPA containing solutions, while the UVC/S2O82– process had a better efficiency in comparison to UVC/H2O2. This behavior is due to the generation of high oxidation power radicals (mainly HO• and SO4•−) by the activation of H2O2, S2O82–, and HClO under UVC light. Considering the oxidation by-products generated, no organochlorine compounds were detected (after 6 h) using UVC/HClO contrasting to the results obtained using only HClO (two organochlorines were detected). In addition, taking into account the environmental (experimental and theoretical toxicity tests) and economical parameters investigated, the UVC/HClO method showed a higher efficiency under low operating costs. However, under complex experimental conditions, more mature technologies such as UVC/H2O2 and UVC/S2O82− are recommended. In this sense, simultaneous elimination of six OMCs (ACT, CAF, CBZ, TMP, SMX, and DCF) and three bacteria (E. coli, E. faecalis, and S. enteritidis) by UVC/H2O2 and UVC/S2O82− processes from a simulated municipal wastewater effluent were successfully investigated at pilot plant scale. UVC AOPs were compared in terms of the required treatment time to remove at least 80% of the sum of OMCs, bacterial inactivation and regrowth, and energy consumption. UVC treatment alone was not suitable mainly due to the very slow and incomplete removal of OMCs, while UVC/H2O2 and UVC/S2O82− were effective to simultaneously eliminate OMCs and bacteria; however, in comparison with the UVC/S2O82 system, the UVC/H2O2 process did not exhibit bacterial regrowth under dark conditions. According to these results and taking into account some environmental regulations, reclaimed water treated with the UVC/H2O2 process is a real alternative for water reuse purposes in many activities, for instance, in agriculture since this activity demands the highest freshwater consumption worldwide. Finally, a simple model based on the Beer–Lambert law enabled reasonable estimation of the oxidant concentration required to attain maximum oxidation rates (i.e., shortest reactions time).
Processos oxidativos avançados baseados em UVC e aplicados no tratamento de águas: estudos em bancada e em escala piloto
Keywords: Processos oxidativos avançados; Tratamento de águas; Reações radicalares; Mecanismo de oxidação; Contaminantes orgânicos emergentes; Bactérias; CIENCIAS EXATAS E DA TERRA::QUIMICA; ENGENHARIAS::ENGENHARIA SANITARIA::TRATAMENTO DE AGUAS DE ABASTECIMENTO E RESIDUARIAS; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA